(untitled) (Journal of Laboratory Animal Science, 2024)
Contagious agalactia is a disease predominantly of milking sheep and goats caused mainly by Mycoplasma agalactiae, clinically manifested as mastitis, arthritis, keratoconjunctivitis and pneumonia. Pathological changes in the mammary gland of rabbits following intra-mammary inoculation of M. agalactiae were studied. Clinical mastitis developed within 24 hpi. It was initially acute but became chronic by the end of the experiment at 9 dpi. The disease was characterized by atrophy of the infected mammary glands, resulting in marked agalactia. Histopathology revealed that the mastitis was acute and purulent initially, followed by infiltration of mononuclear cells with fibroplasia in the interacinar tissue, and later by massive fibrosis by 9 dpi.